2019
DOI: 10.1016/j.ejca.2018.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of Kaposi's sarcoma: European consensus-based interdisciplinary guideline (EDF/EADO/EORTC)

Abstract: Kaposi's sarcoma (KS) is a multifocal neoplasm of lymphatic endothelium-derived cells infected with human herpesvirus 8. Four clinical subtypes are distinguished: the classic, the endemic, the epidemic subtype in HIV positive patients and the iatrogenic subtype. The diagnosis is primarily based on clinical features and confirmation by histology with immunohistochemistry. Cutaneous distribution and severity, mucosal, nodal and visceral involvement depend on the type of KS with in general indolent behaviour and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
213
2
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(242 citation statements)
references
References 89 publications
4
213
2
23
Order By: Relevance
“…This is to be welcomed as these pathological conditions affect millions of people globally and offer limited therapeutic options to patients so far. 21,22 Importantly, the observed in vitro effects of CBD occur at concentrations achieved in humans with well-tolerated therapeutic doses of Epidiolex (up to 20 mg per kg of body weight per day), 23 suggesting that these findings might be easily translated into clinics. However, there is evidence that, other cannabinoids such as D 9 -THC may instead enhance infection and replication of KSHV and promote KSHV-induced endothelial transformation.…”
Section: Discussionmentioning
confidence: 99%
“…This is to be welcomed as these pathological conditions affect millions of people globally and offer limited therapeutic options to patients so far. 21,22 Importantly, the observed in vitro effects of CBD occur at concentrations achieved in humans with well-tolerated therapeutic doses of Epidiolex (up to 20 mg per kg of body weight per day), 23 suggesting that these findings might be easily translated into clinics. However, there is evidence that, other cannabinoids such as D 9 -THC may instead enhance infection and replication of KSHV and promote KSHV-induced endothelial transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, European consensus-based interdisciplinary guidelines state that endoscopy is not strongly recommended for patients with CKS [30]. In these guidelines, endoscopy (as well as bronchoscopy and total-body CT) is recommended to be performed just according to symptoms in both staging work-up and follow-up for patients with all types of KS [30]. This raises the question as to why endoscopy does not appear to be important in the examination of patients with CKS.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question as to why endoscopy does not appear to be important in the examination of patients with CKS. The following two reasons have been indicated: (i) According to some studies, visceral involvement of CKS was reported to be only <10%, which is apparently less than that of other KS [7,30]. Further, a recent report stated that the follow-up interval for patients with CKS can be every 6-12 months, essentially based on clinical examination [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaposi sarcoma-associated herpesvirus (KSHV, also known as Human Herpesvirus-8) is always involved in its aetiology via endothelial infection 1. In the cutaneous presentation of KS, topical agents and physical therapies such as surgical removal,3 cryosurgery,4 imiquimod, laser, radiotherapy,5 and intralesional and systemic chemotherapy5 have been used even though for the AIDS-associated variant, the most effective treatment is antiretroviral therapy 5. There are only limited reports in literature of PDT usage for KS 6,7.…”
mentioning
confidence: 99%